Advances in Versatile GeTe Thermoelectrics from Materials to Devices - Hong, Min; Li, Meng; Wang, Yuan; Shi, Xiao‐Lei; Chen, Zhi‐Gang (Advanced materials (Weinheim), 2023)
Driven by the intensive efforts in the development of high‐performance GeTe thermoelectrics for mass‐market application in power generation and refrigeration, GeTe‐based materials display a high figure of merit of >2.0 and an energy conversion efficiency beyond 10%. However, a comprehensive review on GeTe, from fundamentals to devices, is still needed. In this regard, the latest progress on the state‐of‐the‐art GeTe is timely reviewed. The phase transition, intrinsic high carrier concentration, and multiple band edges of GeTe are fundamentally analyzed from the perspectives of the native atomic orbital, chemical bonding, and lattice defects. Then, the fabrication methods are summarized with a focus on large‐scale production. Afterward, the strategies for enhancing electronic transports of GeTe by energy filtering effect, resonance doping, band convergence, and Rashba band splitting, and the methods for strengthening phonon scatterings via nanoprecipitates, planar vacancies, and superlattices, are comprehensively reviewed. Besides, the device assembly and performance are highlighted. In the end, future research directions are concluded and proposed, which enlighten the development of broader thermoelectric materials. The phase transition, multiple valence bands, and resonant bonding endow GeTe with promising thermoelectric performance. Significant breakthroughs are achieved in GeTe‐based materials. This review summarizes the recent progress in developing high‐performance GeTe‐based materials and devices, including the underlying fundamentals, large‐scale production, novel strategies for boosting performance, and techniques of device assembly.